1992
DOI: 10.1042/bj2870457
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic identification of the haem axial ligands of haemoferritin and location of possible haem-binding sites in ferritin by molecular modelling

Abstract: Horse spleen ferritin will bind up to 16 protoporphyrin IX haem groups per 24 subunits in vitro [Kadir & Moore (1990) FEBS Lett. 276, 81-84] at a site that causes the haem to be low spin for both ferric and ferrous states. E.p.r. spectra at 10 K of the oxidized form of the resulting haemoferritin gives g values of 2.93, 2.26 and 1.55, characteristic of low-spin haem. The near-i.r. magnetic circular dichroism spectrum shows a porphyrin-to-ferric charge-transfer band at 1590 nm. The spectroscopic parameters indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, in vitro studies showed that it was also possible to incorporate hemin (Fe(III)-PPIX) into horse spleen apoferritin [21]. From electron paramagnetic resonance (EPR), near-infrared magnetic circular dichroism (NIR-MCD) and molecular modelling studies, it was suggested that the heme-binding site was situated around the 3-fold symmetry axes and that the ligands of the heme iron were His 114 and His 124 [22]. However, crystallographic studies of horse spleen apoferritin cocrystallised with Sn(II)-protoporphyrin IX (PPIX) or with Fe(III)-PPIX (hemin), showed that the metal-free PPIX was bound in a hydrophobic pocket along the 2-fold symmetry axes [1,23].…”
Section: Introductionmentioning
confidence: 99%
“…However, in vitro studies showed that it was also possible to incorporate hemin (Fe(III)-PPIX) into horse spleen apoferritin [21]. From electron paramagnetic resonance (EPR), near-infrared magnetic circular dichroism (NIR-MCD) and molecular modelling studies, it was suggested that the heme-binding site was situated around the 3-fold symmetry axes and that the ligands of the heme iron were His 114 and His 124 [22]. However, crystallographic studies of horse spleen apoferritin cocrystallised with Sn(II)-protoporphyrin IX (PPIX) or with Fe(III)-PPIX (hemin), showed that the metal-free PPIX was bound in a hydrophobic pocket along the 2-fold symmetry axes [1,23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous spectroscopic and molecular modelling results (Moore et al, 1992) suggested the haem group is probably bound by two histidine ligands, in the region of the threefold axis. Nothing in the structure of the complex reported here suggests that there are two kinds of haem-binding sites in a ferritin molecule.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of a crystallographic study of the haem-binding site in ferritin, even if, during the writing of this paper, the low-resolution structure of bacterioferritin has been solved providing evidence of a nearly similar location of the haem molecule in this structurally related protein (Yariv, 1993). Besides these results, the structure of mammalian ferritin offers no indication of a haembinding site (Moore et al, 1992).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…'^ A first location of the possible binding sites, in ferritin, has been proposed by molecular modeling and spectroscopic investigations. 16 To describe these binding properties further, preliminary results of a crystallographic study17 of HSF co-crystallized with Snprotoporphyrin IX (PDB entry code: 1HRS) allowed us to assign clearly the location of the binding site among the two previously16 predicted sets of sites.…”
mentioning
confidence: 99%